The Merdeka Curriculum Reform on Aspects of Historical Thinking Skills in History Subjects in Senior High Schools - Kuwoto, M. Ari; Yulifar, Leli; Ma’mur, Tarunasena (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The aims of this research are (1) to plan history learning using the Merdeka curriculum for historical thinking skills, (2) to improve the Merdeka curriculum in relation to aspects of history learning for historical thinking skills, and (3) As an evaluation of history teaching and learning activities based on thinking skills. Merdeka Curriculum Aspects of Historical Thinking Skills in SMA Pasundan 2 Cimahi, Especially in Schools that Implement the Merdeka Curriculum. This research applies qualitative methods with a case study approach. The data sources are informants: teachers, students, documents, curriculum, and historical thinking skills. Research findings show that (1) Merdeka Curriculum history learning planning is carried out by teachers who prepare their own ATP and learning modules; However, one of the schools where he could use KOSP was closed, and the teachers at both schools did not know the whereabouts and contents of his KOSP. (2) Implementation of history learning depends on student performance. There are several learning processes that do not follow learning principles, such as Education modules that are not prepared. PLP students take classes based on a unique curriculum. There are no student teaching evaluations for teachers. There are also monotonous learning methods, less situational learning, and unused social studies books. (3) In evaluating teaching and learning activities, there are several cases where the implementation does not follow the principles of teaching and learning evaluation based on the Merdeka Curriculum. Teaching and learning activities in history classes are not in line with assessment principles. There are no student self-assessments or peer assessments, no in-module assessment rubrics, and no post-test quizzes. However, teachers have tried to adhere to some principles and implement their own curriculum as closely as possible. Implementing the Merdeka Curriculum from the perspective of historical thinking skills in history education can be adapted to the implementation of the Merdeka Curriculum established by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia.